Pokrovsky – Rubakin Bridge Theory: a Modern Reading - V. K. Stepanov (Библиосфера)
The development of digital technologies, which provide unprecedented growth in labor productivity, leads to the depreciation of material goods, resulting in the loss of habitual life guidelines for an ever-expanding share of the planet’s population. The purpose of the article is to determine the directions for transforming the activities of a public library, basing on the analysis of the current needs of residents of highly developed countries. Public library, in the author opinion, should become a place where each user will have the opportunity to come to a deep understanding of their own existence, discover talents and gain a stable life position through integration into intellectual and creative activity. The idea of mandatory gradualism – “step-by-step” nature of this process is drawn from the creative heritage of N. A. Rubakin and A. A. Pokrovsky, who developed and put into practice the “theory of bridges” – an approach to the work of libraries that involved the gradual development of reading taste, ultimately aimed at the development of a harmonious personality. The author comes to the conclusion that the current task of libraries is to build bridges from primitive forms of creative activity to more and more meaningful and complicated one with the ultimate goal of leading each user to independent conscious creativity that helps to demonstrate all person’s abilities. As an example, the author provides the list of library services designed to work with segments of the teenage audience identified on the basis of “lifestyle,” which will allow them to unlock the potential of young users and help them to achieve intellectual and creative self-realization.